SALES ANALYSIS OF PRECIOUS METAL, CAPITAL, TOTAL ASSETS, AND OPERATIONAL COSTS ON INCOME LEVELS OF PT. PEGADAIAN SYARIAH PERIOD 2016-2019 - Yuliana; Ismaulina (J-ISCAN: Journal of Islamic Accounting Research, 2021)
The purpose of this study was to determine the effect of selling precious metals, capital, total assets and operating costs on Sharia Pawnshop income for the period 2016-2019. The method in this research uses quantitative methods. The sample in this study is the 2016-2019 financial statements. Data analysis used multiple linear regression analysis using the SPSS program with a significance level of 5% (0.05) The results showed that the variable sales of precious metals and capital had a significant effect on Sharia Pawnshop income. This is indicated by the value of the t-count variable sales of precious metals and capital is greater than the t-table and is at a significant level smaller than 0.05. The variables of total assets and operating costs do not affect Sharia Pawnshop income. This is indicated by the value of the acount of total assets and operating costs is smaller than the t table and is at a significant level greater than 0.05.